Determinación del costo de producción de uniformes en la empresa Maitex sport de la ciudad de Santo Domingo, periodo: abril/mayo 2015 - Ajila Pinzón, Fanny Raquel (2016)
The DETERMINATION OF COST OF PRODUCTION OF UNIFORM IN THE COMPANY MAITEX SPORT IN SANTO DOMINGO CITY, PERIOD: APRIL/MAY 2015, has been realized with the approach of providing clear and concise information about the real cost of products manufactured by the company for the benefit of Mrs. Maira Mireya Ajila Pinzon, based on the Academic Regime Regulation of the National University of Loja, previous to obtain the degree of Engineer in Accounting and Auditing, CPA. Compliance was given to the objectives with the development of a Plan and Manual of Auditors also proceeded to classify and determine the initial inventory, then the file and chronological order of accounting information is performed sequentially production orders designed and requisitioning, as well as the kardex cards; the clock and time worksheet and cards. The budget of indirect manufacturing costs applied in the preparation of production was also developed. And finally the accounts were developed to record the economic activities of the company, noting Accounting Standards applied. Based on the work done, it is concluded that the determination of the production cost of uniforms in the company Maitex Sport provides reliable, timely, real and easy to use information that will allow its owner to know the real costs of the output produced and will serve as a guide for the correct decision making, to thereby seek growth and profit of your company, so it is recommended to continue to maintain its application to be an effective tool to keep the acquired knowledge and to create opportunities for best results.